A COMPARATIVE ANALYSIS OF MFEP AND SAW METHODS IN DECISION SUPPORT SYSTEMS FOR MAJOR SELECTION - Hutahaean, Jeperson; Mulyani, Neni; Putri Fahdrina, Jihan Aulia (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: The selection of majors at SMAS YPK Kedaisianam previously still used a manual system that was less effective in determining the right major for students. To overcome this, a new system that is easier and more accurate is needed. This system is expected to assist counseling guidance teachers in providing solutions for choosing majors to students. This study compares two methods, namely Multi Factor Evaluation Process (MFEP) and Simple Additive Weighting (SAW), which have similarities in weighting criteria to produce more effective rankings. The research methodology used is a quantitative approach with numerical data analysis. This study aims to describe the comparison of the two methods in the decision support system for choosing majors at SMKS DAAR Muhsinin. The results of the study show that the use of more effective methods in the application system can make decision-making easier. The conclusion of this study is that the application of MFEP methods can improve accuracy and efficiency in the course selection process.Keywords: decision support system; mfep and saw methods; major selection. Abstrak: Pemilihan jurusan di SMAS YPK Kedaisianam sebelumnya masih menggunakan sistem manual yang kurang efektif dalam menentukan jurusan yang tepat bagi siswa. Untuk mengatasi hal tersebut, diperlukan sistem baru yang lebih mudah dan akurat. Sistem ini diharapkan membantu guru bimbingan konseling dalam memberikan solusi pemilihan jurusan kepada siswa. Penelitian ini membandingkan dua metode, yaitu Multi Factor Evaluation Process (MFEP) dan Simple Additive Weighting (SAW), yang memiliki kesamaan dalam pembobotan kriteria untuk menghasilkan peringkat yang lebih efektif. Metodologi penelitian yang digunakan adalah pendekatan kuantitatif dengan analisis data berbasis angka. Penelitian ini bertujuan untuk mendeskripsikan perbandingan kedua metode tersebut dalam sistem pendukung keputusan pemilihan jurusan di SMKS DAAR Muhsinin. Hasil penelitian menunjukkan bahwa penggunaan metode yang lebih efektif dalam sistem aplikasi dapat mempermudah pengambilan keputusan. Simpulan dari penelitian ini adalah penerapan metode MFEP dapat meningkatkan akurasi dan efisiensi dalam proses pemilihan jurusan.Kata Kunci: metode mfep dan saw;  pemilihan jurusan; sistem pendukung keputusan.